Composite grouting material as well as preparation method, construction method and application thereof
By adding sulfur aluminate cement clinker powder, silicate cement clinker powder, reinforcement, coagulant and modifier to the grouting material, the composite grouting material is solved, and the problems of poor sprinkling and long gel time in the treatment of sludge from the existing grouting materials in the subway bed sludge pouring and mud pouring treatment are achieved with efficient, economical and environmentally friendly grouting effect.
Patent Information
- Application Number
- CN202411851646.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-28
AI Technical Summary
The existing grouting materials have problems such as poor sprinkling, long gel time, plastic shrinkage, low early strength, unstable volume, poor durability, poor economy and insufficient environmental protection in the treatment of subway bed sludge, which is difficult to meet the rapid demand for subway operation and maintenance.
A composite grouting material is adopted, including sulfur-aluminate cement clinker powder, silicate cement clinker powder, reinforcement, coagulant and modifier. Through ultra-fine powder grinding and alkali excitation reaction, a high-density, early strength and high-strength grouting material is formed. It has the advantages of good pumping, fast gel time, no plastic shrinkage, high early strength, good volume stability, strong durability, appropriate price, environmental protection and non-toxicity.
This composite grouting material meets the needs of rapid grouting and maintenance during the subway operation window period, provides efficient roadbed reinforcement and water blocking effects, extends the service life of the material, reduces maintenance costs, and meets environmental protection requirements.
Smart Images

Figure BDA0005190737500000101 
Figure BDA0005190737500000111 
Figure BDA0005190737500000121
Abstract
Description
Technical Field
[0001] The invention belongs to the field of grouting materials, and more specifically, relates to a composite grouting material and a preparation method, a construction method and an application thereof. Background Art
[0002] Under the influence of various factors such as long-term train vibration, hydrogeological conditions, construction quality and surrounding engineering activities, the integral roadbed of subway tunnels will gradually peel off and become hollow from the lower structure of the tunnel in some sections. As a result, water in the surrounding rock will seep out from the roadbed through structural cracks, and then the leakage water will erode the roadbed, causing the roadbed and its lower structure concrete to vibrate and grind to generate mud, and precipitate fine sand. When the train passes through, the mud and fine sand will overflow from various gaps in the roadbed and ditch surface, forming a mud-swelling phenomenon, which will eventually cause the entire roadbed to become hollow, seriously affecting the safe operation of rail transit.
[0003] Currently, the most recognized feasible control measure is to reinforce the weak areas under the integral roadbed, the loose concrete areas, the gaps in the bonding surface and other defects by grouting. The grouting materials commonly used are ordinary cement, superfine cement, fast-hardening sulphoaluminate cement and other materials.
[0004] Ordinary cement has good injectability, and a larger grouting volume and grouting reinforcement range can be obtained during grouting. The stone body has high strength and can effectively play a reinforcement role. However, ordinary cement single-liquid slurry has poor anti-dispersion performance and is easily dispersed and diluted by water, affecting its strength and water plugging performance. Moreover, due to its large shrinkage rate, there will still be obvious voids after hardening, and the filling effect is poor. It is difficult to penetrate under dense clay and tiny cracks, and can only penetrate into cracks of 0.5mm.
[0005] The superfine cement slurry has high compressive and shear strength, and has the characteristics of early strength and high strength, and can achieve better grouting reinforcement effect; and the superfine cement particles are small in size and have strong injectability. The penetration grouting can be injected into fine cracks, which can achieve better water blocking and reinforcement effects, but its final setting time is long and it is easily dispersed and diluted by water; in addition, hardening shrinkage is also the main limiting factor for its use, especially under large water-cement ratio conditions, the shrinkage is particularly obvious.
[0006] Sulphoaluminate cement has the advantages of early strength and fast hardening, making it suitable for grouting in de-voided areas and cavities. However, its hardening shrinkage effect is obvious, the filling effect is insufficient, the material expansion rate is large, and it is easy to produce large expansion pressure on the structure. In addition, sulphoaluminate cement is relatively expensive and relatively poor in economy.
[0007] The commonly used ordinary cement-water glass double liquid slurry has good injectability and is suitable for temporary water plugging, controlling the scope of grouting reinforcement, and rapid plugging of slurry stop wall leakage. However, its late strength of the binder is low, it is easily decomposed by long-term immersion in water, and the binder has poor durability and large shrinkage rate, making it unsuitable for the treatment of roadbed diseases.
[0008] Chemical grouting materials have obvious advantages over traditional grouting materials such as cement and water glass in terms of injectability, strength, and water-stopping effect, but they are expensive and not suitable for large-scale grouting construction. General chemical grouting materials such as polyurethane grouting materials are mainly used to block sudden water gushing, large-force water leakage and other urgent and dangerous situations. In today's Chinese society, which is increasingly paying attention to green sustainable development and environmental protection, chemical grouting materials have great limitations, especially in the grouting management of water conservancy projects, urban subway tunnels and underground projects in environmentally sensitive areas. Chemical grouting materials are directly prohibited. In a humid environment, the strength of the slurry stone body and the reinforcement of the chemical grouting material is easy to fail, especially in the environment of complex underground water movement, seepage, acid and alkali and ion corrosion, its performance decreases rapidly, which does not meet the requirements of high durability of materials for tunnels and underground projects during the full service life.
[0009] In view of the short maintenance window of subway operation, common maintenance materials still have the problem that the setting time and operability time are not compatible with the requirements of engineering application technology. The construction is often difficult to meet the requirements due to insufficient fluidity or too long setting time. The early strength of grouting materials, especially the half-hour compressive strength, is difficult to meet the requirements. The vibration of train traffic causes the damage of the grouting repair layer and then fails later. Under the premise of meeting the maintenance requirements, the material economy is poor, the maintenance cost is high, and the environmental protection is insufficient. The present invention urgently needs to provide a grouting material for the treatment of mud bubbling and mud bubbling in subway roadbeds through the optimized design of materials. Summary of the invention
[0010] The purpose of the present invention is to propose a composite grouting material and a preparation method and a construction method and application thereof in view of the deficiencies of the prior art. The composite grouting material of the present invention has the advantages of good pumpability, fast gel time, no plastic shrinkage, high early strength, good volume stability, strong durability, reasonable price, environmental protection and non-toxicity, etc., and meets the needs of rapid grouting maintenance during the subway operation window period.
[0011] In order to achieve the above-mentioned object, the first aspect of the present invention provides a composite grouting material, which comprises the following components: sulphoaluminate cement clinker powder, silicate cement clinker powder, a reinforcing agent, a coagulant and a modifier;
[0012] The reinforcing agent comprises: ultrafine mineral powder, ultrafine fly ash, silica ash and calcium sulfate whisker;
[0013] The coagulant comprises: alumina clinker powder, calcium hydroxide, lithium carbonate and aluminum hydroxide;
[0014] The modifiers include shrinkage reducers, thickeners, water reducers and retarders.
[0015] According to the present invention, preferably, the composite grouting material comprises the following components in parts by weight: 20 to 70 parts of sulphoaluminate cement clinker powder, 15 to 70 parts of silicate cement clinker powder, 10 to 30 parts of reinforcing agent, 1 to 10 parts of accelerator and 1 to 10 parts of modifier.
[0016] According to the present invention, preferably, the composite grouting material comprises the following components in parts by weight: 20 to 65 parts of sulphoaluminate cement clinker powder, 15 to 65 parts of silicate cement clinker powder, 10 to 30 parts of reinforcing agent, 1 to 8 parts of accelerator and 1 to 8 parts of modifier.
[0017] According to the present invention, preferably, the reinforcing agent comprises the following components in parts by weight: 25-45 parts of ultrafine mineral powder, 25-45 parts of ultrafine fly ash, 15-35 parts of silica fume and 5-15 parts of calcium sulfate whiskers.
[0018] According to the present invention, preferably, the reinforcing agent comprises the following components in parts by weight: 25-40 parts of ultrafine mineral powder, 25-35 parts of ultrafine fly ash, 20-35 parts of silica fume and 5-15 parts of calcium sulfate whiskers.
[0019] According to the present invention, preferably, the coagulant comprises the following components in parts by weight: 15-45 parts of alumina clinker powder, 20-70 parts of calcium hydroxide, 3-15 parts of lithium carbonate and 3-15 parts of aluminum hydroxide.
[0020] According to the present invention, preferably, the coagulant comprises the following components in parts by weight: 20-40 parts of alumina clinker powder, 40-70 parts of calcium hydroxide, 5-10 parts of lithium carbonate and 5-10 parts of aluminum hydroxide.
[0021] According to the present invention, preferably, the modifier comprises the following components in parts by weight: 5 to 30 parts of shrinkage reducer, 5 to 35 parts of thickener, 25 to 55 parts of water reducer and 5 to 25 parts of retarder.
[0022] According to the present invention, preferably, the modifier comprises the following components in parts by weight: 10 to 25 parts of shrinkage reducer, 8 to 35 parts of thickener, 25 to 52 parts of water reducer and 8 to 25 parts of retarder.
[0023] According to the present invention, preferably, the sulphoaluminate cement clinker powder is obtained by crushing, grinding and passing through a 75-85 μm square hole sieve of sulphoaluminate cement clinker.
[0024] According to the present invention, preferably, the silicate cement clinker powder is obtained by crushing, grinding and passing through a 75-85 μm square hole sieve of silicate cement clinker.
[0025] According to the present invention, preferably, the particle size of the ultrafine fly ash is ≤10 μm.
[0026] The second aspect of the present invention provides a method for preparing the composite grouting material, the method comprising the following steps:
[0027] S1: mixing and grinding sulphoaluminate cement clinker powder, silicate cement clinker powder and a reinforcing agent to obtain a powder;
[0028] S2: The powder is mixed with a coagulant and a modifier and stirred uniformly to obtain the composite grouting material.
[0029] According to the present invention, preferably, in step S1, the equipment used for grinding includes a jet mill; the specific surface area of the powder is 700-1700m 2 / Kg.
[0030] In the present invention, sulphoaluminate cement clinker powder, silicate cement clinker powder and a reinforcing agent are mixed to obtain a premix, which is then placed in a jet mill, and the premix is subjected to impact, shearing and friction by a high-speed airflow to achieve ultrafine grinding.
[0031] According to the present invention, preferably, in step S2, the equipment used for mixing and stirring includes a dry mortar mixer, and the mixing and stirring time is 3-10 minutes.
[0032] The third aspect of the present invention provides a construction method of the composite grouting material, comprising mixing the composite grouting material and water uniformly with a putty mixer to obtain slurry, and performing grouting construction;
[0033] According to the present invention, preferably, the water-cement ratio of the composite grouting material is (0.2-0.55):1;
[0034] According to the present invention, preferably, the stirring rate of the putty mixer is 50-2500 rpm and the stirring time is 2-10 min.
[0035] In the present invention, the mixing effect of the slurry is related to the stirring time and rotation speed of the putty mixer. As a preferred embodiment, when the stirring speed of the putty mixer is 500 rpm, it is preferably stirred for 8 minutes; when the stirring speed of the putty mixer is 2000 rpm, the stirring time can be shortened to 3 minutes.
[0036] The fourth aspect of the present invention provides the use of the composite grouting material in at least one of the following treatments: mud bubbling on subway roadbeds, filling and reinforcing concrete cracks in subway tunnel segments, grouting and water-stopping of secondary lining concrete cracks, and rapid backfilling behind primary supports.
[0037] The beneficial effects of the technical solution of the present invention are as follows: the composite grouting material for subway roadbed slurry and mud treatment of the present invention not only has the advantages of good pumpability, fast gel time, no plastic shrinkage, high early strength, good volume stability, strong durability, suitable price, environmental protection and non-toxicity, but also has the characteristics of adapting to existing construction processes. The slurry can maintain good fluidity and stability for a long time within a set time, so that it can meet the needs of rapid grouting maintenance within the subway operation window period. Specifically:
[0038] 1. Both sulphoaluminate cement clinker powder and silicate cement clinker powder are hydraulic cementitious materials, and their hydration products are mainly CSH gel, calcium hydroxide, calcium sulfonate, hydrated aluminate gel and other minerals. The two are the basis of current cement-based grouting materials. Since no mixed materials are added to the two clinker powders, the mineral components in the clinker can be more clearly defined, which is more conducive to achieving the material performance indicators required in the design of the present invention. The present invention is designed based on the two clinker powders, and the chemical composition and mineral components of cement clinker are more accurately grasped, providing a theoretical basis for performance indicators such as material setting time, early strength, and later stability.
[0039] 2. Strengthening agent, in which the glassy body accounts for more than 90% of the ultrafine mineral powder, and has a high hydration activity under alkali-activated conditions, which is beneficial to improve the overall density of the material and increase the strength; ultrafine fly ash is generally ground to ≤10μm. Since the fly ash contains more than 50% of glassy components, it has a certain hydration activity and is easily activated by alkali, thereby improving the strength. At the same time, fly ash particles are generally spherical, and their fluidity is higher under the action of water reducer, which is beneficial to the flow of slurry and reduces grouting pressure; silica ash contains a large amount of non-crystalline silicon dioxide, which has a large specific surface area and high activity, thereby improving the performance of the stone body, thereby improving the material strength and impermeability indicators; the average diameter of calcium sulfate whiskers is 1-4μm, and the average length is 2-6μm. Compared with ordinary gypsum, the addition of calcium sulfate whisker material can greatly increase the formation rate and content of calcium sulfide. Calcium sulfate whiskers react with calcium hydroxide and aluminum hydroxide to generate more calcium sulfide seeds, which then grow into calcium sulfide crystals, and then form a fibrous network system of calcium sulfide, achieving high strength and impermeability. The present invention introduces ultrafine inorganic powder minerals such as ultrafine mineral powder, silica fume, and ultrafine fly ash, so that a large amount of new active gels such as hydrated calcium silicate and hydrated calcium aluminate are formed in the hydration process of the composite grouting material, which fully fills the free water pores, improves the density of the stone body, increases the strength of the grouting stone body, helps to fill the cracks in the roadbed concrete, and achieves a good anti-seepage effect.
[0040] 3. The coagulant does not contain chloride ion substances, thus avoiding adverse effects on concrete reinforcement. The combined effect of alumina clinker powder, calcium hydroxide, lithium carbonate, and aluminum hydroxide can not only act as the alkaline activator to activate the hydration of ultrafine fly ash, ultrafine mineral powder, silica fume and other low-activity cementitious materials, but also adjust the gel time of the slurry, which is more conducive to accurately controlling the curing time of the slurry, quickly enhancing the early strength of the material, increasing the content of later hydrated minerals and the density of the stone body, and improving the degree of consolidation in concrete cracks. And with the migration of the effective ingredients of the alkaline activator, it can further react with the hydration products in the original concrete to generate more hydrated crystal products, seal microcracks, and achieve the self-healing of concrete defects.
[0041] 4. The combined effect of multiple components of the coagulant can not only improve the early strength of the cement stone body, promote the hydration degree and hydration formation rate of the hydrated minerals in the composite grouting material system, but also make up for the deficiency of a single coagulant in reducing the strength of the hydration product after solidification. In addition, through the micro-expansion characteristics of sulphoaluminate cement clinker powder and silicate cement clinker powder reacting with calcium hydroxide, aluminum hydroxide, calcium sulfate (calcium sulfate whiskers), active silica, etc., the volume shrinkage of the material injected into the cracks of the concrete can be prevented, so that the stone body of the material can be effectively combined with the concrete to form a good reinforcement body, jointly bear the force of structural conduction, prevent secondary cracking caused by train vibration, and strengthen the effect of grouting treatment.
[0042] 5. Modifiers, whose main function is to adjust the construction performance of materials and ensure the stability of slurry. The water reducer, thickener, shrinkage reducer and retarder all have their own functions. The plasticizing effect of the water reducer can reduce the water consumption of the slurry and improve the fluidity; the thickener can not only effectively control the suspension stability of the slurry, reduce water seepage and segregation, but also effectively improve the stability during the grouting construction process. At the same time, it is injected into the water-containing gap to make the slurry have a certain water resistance and dispersion ability, reduce the dilution of the material, and avoid strength loss; the shrinkage reducer can effectively prevent the composite grouting material from changing its volume due to the reduction of water during the consolidation process, and synergize with the thickener to effectively prevent the shrinkage and degassing of the grouting slurry; the retarder can prolong the hydration time of cement particles to avoid the occurrence of rapid setting and explosion, which will shorten the operating time of the grouting slurry and make it impossible to carry out grouting construction. The present invention selects and designs the reasonable action mechanism of the retarder and the accelerator, and the two are reasonably matched to play a better synergistic effect, which not only meets the window period operation time requirements, but also ensures that the material can have enough operational time and grouting diffusion time, so as to more accurately control the grouting range, avoid the adverse effects of grouting on rail transit, and reduce material waste. By adjusting the working performance of the slurry by the modifier, it is finally guaranteed that the construction is carried out efficiently during the subway window period. The composite grouting material of the present invention not only has higher compressive strength at a low water-cement ratio, but also has higher fluidity. On the basis of improving the construction performance of the material, the slurry is more conducive to filling the holes and gaps of the concrete; when the composite grouting material of the present invention has a higher water-cement ratio, the modifier in the material makes the slurry have excellent water retention performance, without sedimentation and water seepage, and the slurry has good water resistance and dispersibility during the grouting process, and is not easily diluted by water in the cracks.
[0043] 6. The present invention can effectively prevent the volume change of the slurry due to the reduction of water content in the composite grouting material during the consolidation process by adding a variety of substances (modifiers) that resist plastic shrinkage, avoid plastic shrinkage, and improve the grouting density, thereby avoiding the phenomenon of voids caused by insufficient slurry filling the cracks in the ballast concrete, and changing the phenomenon in traditional processes that although the grouting is dense, slurry settlement voids will appear in the later stage.
[0044] 7. The present invention uses the ultra-fine grinding effect of the high-speed airflow mill to make the material reach the micron level, the material hydration effect is more complete, the hydration products are more, the stone body is denser, and the fine cracks at the crack position of the roadbed concrete can be effectively blocked. At the same time, the alkali-activated components in the coagulant are more conducive to the Ca in the original concrete. 2+ 、SiO 4- 、AlO4 5- The materials are combined and reassembled into a self-compacting structure to achieve self-healing of fine cracks and prevent the cross-flow of free water.
[0045] 8. The composite grouting material of the present invention can achieve a compressive strength of 22 MPa in half an hour and 30 MPa in 1 hour. It is densely combined with concrete and can fully meet the pressure-bearing requirements of the roadbed when subway trains pass through after maintenance. The present invention effectively solves the problem that the current grouting material has too low strength after grouting, is very easy to be damaged twice during transportation, and has to be repaired and leaked repeatedly.
[0046] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION
[0047] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.
[0048] In the following embodiments and comparative examples:
[0049] Sulphoaluminate cement clinker is SACC-I type sulphoaluminate cement clinker that complies with GB / T 37125-2018.
[0050] Portland cement clinker is general cement clinker that conforms to GB / T21372-2024.
[0051] The ultrafine mineral powder is S95 type slag powder that complies with GB / T18046-2017.
[0052] Ultrafine fly ash is fly ash for cement active admixture that complies with GB / T 1596-2017.
[0053] The silica fume is SF90 type silica fume that complies with GB / T 27690-2023.
[0054] The calcium sulfate whiskers are DX300 ultrafine calcium sulfate whiskers produced by Shenzhen Chaobang New Energy Materials Co., Ltd.
[0055] Alumina clinker is FSA-AF type accelerating agent which complies with GB / T 35159-2017.
[0056] Calcium hydroxide is a white powder of calcium hydroxide of type 90 or above that conforms to HG / T4120-2024.
[0057] Lithium carbonate is white powdered lithium carbonate of type Li2CO3-1 that complies with GB / T 11075-2013.
[0058] Aluminum hydroxide is AH-1 type white powder aluminum hydroxide that complies with GB / T 4294-2010.
[0059] The shrinkage reducing agent is Yingshan EP-03 shrinkage reducing agent produced by Shanghai Yingshan New Material Technology Co., Ltd., and the product is a powder.
[0060] The thickener is HEMC with a viscosity of 40,000 in accordance with JC / T 2190-2013, a powdered product.
[0061] The water reducer is a polycarboxylic acid high performance water reducer RS type powder product that complies with JG / T 223-2017.
[0062] The retarder is dl-tartaric acid (anhydrous) in accordance with GB 15358-2008.
[0063] Example 1
[0064] The present embodiment provides a composite grouting material, which includes the following components in parts by weight: 60 parts of sulphoaluminate cement clinker powder, 20 parts of silicate cement clinker powder, 12 parts of a reinforcing agent, 5 parts of a coagulant, and 3 parts of a modifier;
[0065] The reinforcing agent comprises the following components in parts by weight: 30 parts of ultrafine mineral powder, 30 parts of ultrafine fly ash, 30 parts of silica fume and 10 parts of calcium sulfate whisker;
[0066] The coagulant comprises the following components in parts by weight: 30 parts of alumina clinker powder, 50 parts of calcium hydroxide, 10 parts of lithium carbonate and 10 parts of aluminum hydroxide;
[0067] The modifier includes the following components in parts by weight: 20 parts of shrinkage reducer, 30 parts of thickener, 30 parts of water reducer and 20 parts of retarder.
[0068] The preparation method of the composite grouting material of this embodiment comprises the following steps:
[0069] S1: Sulphoaluminate cement clinker is crushed, ground and passed through a 80μm square hole sieve to obtain sulphoaluminate cement clinker powder; Portland cement clinker is crushed, ground and passed through a 80μm square hole sieve to obtain Portland cement clinker powder; Sulphoaluminate cement clinker powder, Portland cement clinker powder and enhancer are mixed to obtain a premix, and then the premix is put into a jet mill, and the high-speed airflow is used to impact, shear and rub the premix to achieve ultra-fine grinding to obtain a powder with a specific surface area of 800m 2 / Kg;
[0070] S2: Put the powder, coagulant and modifier into a dry mortar mixer and stir quickly for 6 minutes. After mixing evenly, the composite grouting material is obtained.
[0071] In this embodiment, the composite grouting material of this embodiment is applied to the treatment of mud bubbling in subway roadbed, wherein the composite grouting material of this embodiment is prepared at a water-cement ratio of 0.28:1, and the prepared slurry is stirred at 500 rpm by a putty mixer for 8 minutes, and then the grouting construction can be carried out.
[0072] Table 1
[0073]
[0074]
[0075] Test Case
[0076] This test example tests the initial fluidity, water seepage rate, setting time, vertical expansion rate, compressive strength and anti-seepage pressure of the composite grouting materials of the above-mentioned embodiments and comparative examples.
[0077] The initial fluidity is the fluidity index of the slurry after preparation. The test method is determined according to the test method specified in 13 Cement Paste Fluidity in GB / T8077-2012 Test Method for Homogeneity of Concrete Admixtures.
[0078] The water seepage rate is tested according to the method specified in JC / T 2153-2012, and the test results are averaged.
[0079] Setting time, including initial setting time and final setting time, is tested according to the test method specified in GB / T 1346-2011 cement standard consistency water consumption, setting time, and stability test method. The instrument used in the test is a Vicat instrument. Repeat the test 3 times and take the average value of the results.
[0080] Vertical expansion rate: the test method is in accordance with the method specified in GB / T 50448-2015 Technical Specification for Application of Cement-based Grouting Materials, and the vertical expansion rate of the material at initial setting and final setting is determined by non-contact measurement method.
[0081] Compressive strength mainly tests the compressive strength of the consolidated body obtained by the composite grouting material, including the compressive strength of 0.5h, 1h, 1d, 3d and 28d. The molded material is formed according to the method specified in GB / T 17671-2021. Because the material has good fluidity, the test method is modified to not require vibration. The stirred slurry is directly poured into the test mold. In order to prevent the molded specimen from having holes, shrinkage, etc., it should not be shaken before final setting to reduce errors. The test method and data processing are still carried out in accordance with GB / T 17671-2021.
[0082] The impermeability pressure mainly tests the 7d impermeability of the consolidated body obtained by the composite grouting material. The test is carried out according to the method specified in GB 23440-2009, and the test results are averaged.
[0083] The test results are shown in Table 2.
[0084] Table 2
[0085]
[0086] It can be seen from Table 2 that materials such as calcium hydroxide, aluminum sulfate, lithium carbonate, and alumina clinker improve the solidification characteristics of the composite grouting material and can quickly and more stably stimulate the early strength of the material; the application of the shrinkage reducer avoids the plastic shrinkage of the composite grouting material in the early rapid setting stage and improves the grouting density; the present invention effectively controls the setting time of the material and increases the operability during the construction process through the selection and design of the water reducer, the coagulant, and the thickener.
[0087] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A composite grouting material, characterized in that: The composite grouting material comprises the following components: sulphoaluminate cement clinker powder, silicate cement clinker powder, reinforcing agent, accelerator and modifier; The reinforcing agent comprises: ultrafine mineral powder, ultrafine fly ash, silica ash and calcium sulfate whisker; The coagulant comprises: alumina clinker powder, calcium hydroxide, lithium carbonate and aluminum hydroxide; The modifiers include shrinkage reducers, thickeners, water reducers and retarders.
2. The composite grouting material according to claim 1, wherein: The composite grouting material comprises the following components in parts by weight: 20 to 70 parts of sulphoaluminate cement clinker powder, 15 to 70 parts of silicate cement clinker powder, 10 to 30 parts of a reinforcing agent, 1 to 10 parts of a coagulant and 1 to 10 parts of a modifier; Preferably, the composite grouting material comprises the following components in parts by weight: 20 to 65 parts of sulphoaluminate cement clinker powder, 15 to 65 parts of silicate cement clinker powder, 10 to 30 parts of reinforcing agent, 1 to 8 parts of accelerator and 1 to 8 parts of modifier.
3. The composite grouting material according to claim 1, wherein: The reinforcing agent comprises the following components in parts by weight: 25-45 parts of ultrafine mineral powder, 25-45 parts of ultrafine fly ash, 15-35 parts of silica fume and 5-15 parts of calcium sulfate whisker; Preferably, the reinforcing agent comprises the following components in parts by weight: 25-40 parts of ultrafine mineral powder, 25-35 parts of ultrafine fly ash, 20-35 parts of silica fume and 5-15 parts of calcium sulfate whiskers.
4. The composite grouting material according to claim 1, wherein: The coagulant comprises the following components in parts by weight: 15-45 parts of alumina clinker powder, 20-70 parts of calcium hydroxide, 3-15 parts of lithium carbonate and 3-15 parts of aluminum hydroxide; Preferably, the coagulant comprises the following components in parts by weight: 20-40 parts of alumina clinker powder, 40-70 parts of calcium hydroxide, 5-10 parts of lithium carbonate and 5-10 parts of aluminum hydroxide.
5. The composite grouting material according to claim 1, wherein: The modifier comprises the following components in parts by weight: 5 to 30 parts of shrinkage reducer, 5 to 35 parts of thickener, 25 to 55 parts of water reducer and 5 to 25 parts of retarder; Preferably, the modifier comprises the following components in parts by weight: 10 to 25 parts of shrinkage reducer, 8 to 35 parts of thickener, 25 to 52 parts of water reducer and 8 to 25 parts of retarder.
6. The composite grouting material according to claim 1, wherein: The sulphoaluminate cement clinker powder is obtained by crushing, grinding and passing the sulphoaluminate cement clinker through a 75-85 μm square hole sieve; The silicate cement clinker powder is obtained by crushing, grinding and passing through a 75-85 μm square hole sieve of silicate cement clinker; The particle size of the ultrafine fly ash is ≤10 μm.
7. The method for preparing the composite grouting material according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: S1: mixing and grinding sulphoaluminate cement clinker powder, silicate cement clinker powder and a reinforcing agent to obtain a powder; S2: The powder is mixed with a coagulant and a modifier and stirred uniformly to obtain the composite grouting material.
8. The method for preparing the composite grouting material according to claim 7, wherein: In step S1, the equipment used for grinding includes a jet mill; the specific surface area of the powder is 700-1700m 2 / Kg; In step S2, the equipment used for mixing and stirring includes a dry mortar mixer, and the mixing and stirring time is 3-10 minutes.
9. The construction method of the composite grouting material according to any one of claims 1 to 6, characterized in that: The construction method comprises mixing the composite grouting material and water evenly with a putty mixer to obtain slurry, and performing grouting construction; Preferably, the water-cement ratio of the composite grouting material is (0.2-0.55):1; Preferably, the stirring speed of the putty mixer is 50-2500 rpm and the stirring time is 2-10 min.
10. Application of the composite grouting material according to any one of claims 1 to 6 in at least one of the following treatments: mud bubbling on subway roadbed, filling and reinforcing concrete cracks in subway tunnel segments, grouting to stop water seepage from cracks in secondary lining concrete, and rapid backfilling behind primary support.
Citation Information
Cited By
Composite grouting material for water-rich fault fracture zone as well as preparation method and application of composite grouting material
CN120965244A
Green grouting material for rapidly repairing bridge cracks based on modified ceramic powder and preparation method of green grouting material
CN121717599A
Cement-based high-early-strength grouting material as well as preparation method, application and grouting method thereof
CN122380783A